Tablet-Based eBooks for Young Children: What Does the Research Say?. Issue 7 (September 2016) - Reich, Stephanie M.; Yau, Joanna C.; Warschauer, Mark
ABSTRACT: Objective: Young children's use of electronic books (eBooks) is increasing as handheld touch screen devices, such as tablets, become increasingly available. Although older children's reading on tablets has been more broadly investigated, less is known about the impacts of digital reading for infant, toddlers, and preschoolers. This review compares the educational affordances of reading on tablets versus print books for young children's learning. Method: A qualitative synthesis of research on tablet-based eReading and young children's learning from screens was conducted. Results: When eBooks are designed well, preschool-aged children learn equally well and sometimes more than from print books. However, enhanced eBooks with sounds, animations, and games can distract children and reduce learning. When book-sharing with an adult, conversations during eBook reading are often about the platform while print book conversations are more often about the book content. For young children (0–2 yr), there is a paucity of research, but broader studies on learning from screens suggest limited educational benefits of tablet use for this age group. Discussion: The authors recommend that (1) the selection of eBooks (especially enhanced eBooks) be thoughtful as games or animations that are not related to the story content can be distracting for young children, (2) adults share in the reading experience as discussions of the story, text, and characters have been found to enhance comprehension, language development, and print awareness, and (3) tablet eBook use be restricted for infants and toddlers, as they benefit more from face-to-face interaction with caregivers than from interactive screens alone.